The Influence of Classroom Climate and Teachers’ Social Interaction Skills on Academic Development Mediated by the Family Environment (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2026)
This study examines the influence of classroom climate and teachers' social interaction skills on students' academic development, with the family environment as a mediator. Using an associative quantitative approach, data were obtained from 118 sixth-grade students in 13 elementary schools in Kalidawir District through questionnaires and analyzed using SEM-PLS. The results indicate that classroom climate and teachers' social skills have a positive and significant influence on academic development, both directly and indirectly through the family environment. These findings emphasize the importance of creating a conducive classroom atmosphere, communicative teachers, and family support in supporting academic achievement.